Deep Learning-Based Education Management to Increase Student Enrollment at Christian Junior High Schools in Batam - Efvi Noyita (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This study examines the implementation of education management based on deep learning, which combines an intensive pedagogical approach and spiritual values to increase student enrollment in Christian Junior High Schools (SMP) in Batam. With a strategy emphasizing meaningful learning, intensive interaction, and integration of spiritual values, this research aims to analyze how innovative education management can strengthen the appeal of Christian schools and improve overall education quality. A mixed-methods approach was used, collecting quantitative and qualitative data through surveys, interviews, and observations at 36 Christian SMPs in Batam. The results indicate that the synergy between deep learning-based management, curriculum innovation, and spiritual leadership of school principals significantly contributes to enhancing education quality and student enrollment. This article provides practical recommendations for developing school management based on meaningful and spiritual learning as a model for improving the quality and competitiveness of Christian schools in the global era.